2017
DOI: 10.2967/jnumed.117.193649
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and Estrogen Receptor Imaging in Metastatic Breast Cancer Patients as a Surrogate for Tissue Biopsies

Abstract: In addition to the well-known estrogen receptor (ER) and human epidermal growth factor receptor 2, the androgen receptor (AR) is also a potential drug target in breast cancer treatment. Whole-body imaging can provide information across lesions within a patient. ER expression in tumor lesions can be visualized by F-fluoroestradiol (F-FES) PET, and AR expression has been visualized in prostate cancer patients with F-fluorodihydrotestosterone (F-FDHT) PET. Our aim was to assess the concordance between F-FDHT andF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 25 publications
(73 reference statements)
5
55
0
Order By: Relevance
“…While 18 F-FES imaging has many benefits, it does have some limitations related to its ability to detect liver metastases because of the increased uptake of 18 From a sensitivity and specificity perspective, 18 F-FES has a high accuracy for the detection of ER+ lesions; which was illustrated in a meta-analysis conducted on 12 different studies that evaluated patients who had 18 F-FES imaging and compared FES results to biopsy/histopathology staining (Allred) results in patients with breast cancer (30-32, [37][38][39][40][41][42][43][44][45]. The meta-analysis demonstrated that for metastatic lesions, a test sensitivity of 100% and a specificity of 99% (30-32, [37][38][39][40][41][42][43][44][45]. When combined (primary lesion + metastatic lesions), FES imaging resulted in a sensitivity of 81% and a specificity of 80% when compared to biopsy/histopathology results (30-32, 37-45).…”
Section: Potential Benefits Of 18 F-fes Estrogen Receptor (Er) Imagingmentioning
confidence: 99%
“…While 18 F-FES imaging has many benefits, it does have some limitations related to its ability to detect liver metastases because of the increased uptake of 18 From a sensitivity and specificity perspective, 18 F-FES has a high accuracy for the detection of ER+ lesions; which was illustrated in a meta-analysis conducted on 12 different studies that evaluated patients who had 18 F-FES imaging and compared FES results to biopsy/histopathology staining (Allred) results in patients with breast cancer (30-32, [37][38][39][40][41][42][43][44][45]. The meta-analysis demonstrated that for metastatic lesions, a test sensitivity of 100% and a specificity of 99% (30-32, [37][38][39][40][41][42][43][44][45]. When combined (primary lesion + metastatic lesions), FES imaging resulted in a sensitivity of 81% and a specificity of 80% when compared to biopsy/histopathology results (30-32, 37-45).…”
Section: Potential Benefits Of 18 F-fes Estrogen Receptor (Er) Imagingmentioning
confidence: 99%
“…In a metaanalysis of 5 18 F-fluoroestradiol imaging studies with ER immunohistochemistry results (143 patients), pooled sensitivity and specificity were 82% and 95%, respectively (6). In another study of 13 heavily pretreated patients with metastatic ER-positive breast cancer, Venema et al identified 1.54 as the optimal 18 F-fluoroestradiol SUV max cutoff to discriminate ER-positive from ER-negative lesions (7). In a retrospective study of 46 patients with histologically confirmed invasive breast cancer reported by Yang et al, the optimal 18 F-fluoroestradiol threshold was 1.21 for SUV mean and 1.82 for SUV max (8).…”
Section: Assessment Of Er Statusmentioning
confidence: 99%
“…Imaging data for these newer agents has been validated and shown to reflect target expression: a small but intensive study of targeted agents such as 18 F‐DHT and 18 F‐ES (Estradiol) showed that semi‐quantitative androgen or oestrogen receptor expression on immunohistochemistry and 18 F‐DHT or 18 F‐ES uptake respectively on PET was correlated. Moreover, using optimal cut‐offs (SUV max of 1.94 for 18 FDHT‐PET and 1.54 for 18 FES‐PET) sensitivities of 91% and 100% and specificities of 100% and 100% respectively were achieved …”
Section: Imaging For Detecting Omdmentioning
confidence: 99%
“…Moreover, using optimal cut-offs (SUV max of 1.94 for 18 FDHT-PET and 1.54 for 18 FES-PET) sensitivities of 91% and 100% and specificities of 100% and 100% respectively were achieved. 59 Whole-body MRI has the advantage of combining morphological data (T1 and T2-W imaging) with functional information (diffusion-weighted and dynamic contrast-enhanced imaging) thus simultaneously exploiting multiple contrast mechanisms to image and detect the presence of disease. As diffusion-weighted and contrast-enhanced MRI data are fundamentally quantitative, thresholding can be set so that the images display the required sensitivity and specificity.…”
Section: Available Modalitiesmentioning
confidence: 99%